2014
DOI: 10.1002/anie.201309132
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Controlled Switching of an X Ligand into a Z Ligand: Coordination Non‐innocence of a Stiboranyl Ligand

Abstract: The tetravalent platinum stiboranyl complex [(o-(Ph2P)C6H4)2(o-C6Cl4O2)Sb]PtCl2Ph (2) has been synthesized by reaction of [(o-(Ph2P)C6H4)2SbClPh]PtCl (1) with o-chloranil. In the presence of fluoride anions, the stiboranyl moiety of 2 displays non-innocent behavior and is readily converted into a fluorostiborane unit. This transformation, which is accompanied by elimination of a chloride ligand from the Pt center, results in the formation of [(o-(Ph2P)C6H4)2(o-C6Cl4O2)SbF]PtClPh (3). Structural, spectroscopic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 52 publications
2
49
1
Order By: Relevance
“…At the top of the group (N and P) the higher electronegativity,c ombined with the presence of compact lone pairs,i sk nown to lead to ambidentate character in which both the N-atoms of the 2-py groups and the Group 15 atom (E) can donate to metal ions ( Figure 2b). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information).…”
mentioning
confidence: 98%
“…At the top of the group (N and P) the higher electronegativity,c ombined with the presence of compact lone pairs,i sk nown to lead to ambidentate character in which both the N-atoms of the 2-py groups and the Group 15 atom (E) can donate to metal ions ( Figure 2b). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information). [32][33][34][35][36] The increase in the Lewis acidity of the bridgehead atoms in 1-3 was demonstrated by initial DFT (B3LYP/def2-TZVPP) calculations of their fluoride ion affinities (see the Supporting Information).…”
mentioning
confidence: 98%
“…[1] Antimony derivatives,b ecause of their intrinsically higher Lewis acidity, [2] are also drawing considerable attention both in the areas of small-molecule activation and catalysis, [3] as well as in anion complexation. [4] Recent efforts in the chemistry of organoantimony(III) [5] have established that derivatives such as I [6] and II [7] readily bind halide anions ( Figure 1) by donation into the s*orbital (Figure 2). [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1).…”
mentioning
confidence: 99%
“…[6][7][8][9] Sb-M (M = late transition metal) complexes can demonstrate unforeseen reactivity arising from the non-innocence of antimony ligands with respect to redox or coordination, as demonstrated by Gabbaï's extensive work on tethered Sb-M systems, leading to potential applications in catalysis, solar energy storage and anion sensing. 3,[10][11][12][13][14][15][16] In particular, the strong affinity of Sb for halide anions (X -) means that the formation of Sb-X bonds is often favoured over the formation of M-X bonds.…”
Section: Introductionmentioning
confidence: 99%